2022
DOI: 10.22207/jpam.16.4.28
|View full text |Cite
|
Sign up to set email alerts
|

Functional Low-fat Set Yogurt Enhanced with Microbial Exo-polysaccharides-mediated Anticancer Activity

Abstract: Exopolysaccharides (EPSs) are novel functional additives for low-fat yogurt. Pharmaceutical, medical, and food industries are using more LAB-based EPSs. In this study, Leuconostoc spp. was used to produce ninth bacterial EPSs in a modified molasses medium. Production of EPSs was concentration-dependent on all stains and the highest yield was obtained from the S3 strain (55.23 g/l), followed by S6 (49.95 g/l), S8 (45.68 g/l), and S7 (44.23), respectively. HPLC and FTIR analysis showed that all purified EPSs fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 56 publications
0
5
0
Order By: Relevance
“…As discussed in the previous paragraph, ESPs can also affect WHC of yoghurt. Khider et al (2022) demonstrated the impact of EPSs on the water holding capacity of low-fat yoghurt that was fortified with varying concentrations of EPS derived from Leuconostoc strains, in comparison to a control sample. The study revealed a noticeable trend: as the concentration of EPS was elevated, there was a corresponding increase in the water holding capacity of the yoghurt.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…As discussed in the previous paragraph, ESPs can also affect WHC of yoghurt. Khider et al (2022) demonstrated the impact of EPSs on the water holding capacity of low-fat yoghurt that was fortified with varying concentrations of EPS derived from Leuconostoc strains, in comparison to a control sample. The study revealed a noticeable trend: as the concentration of EPS was elevated, there was a corresponding increase in the water holding capacity of the yoghurt.…”
Section: Resultsmentioning
confidence: 99%
“…Another recent study revealed the impact of adding CW to yoghurt samples, noting a significant increase in WHC values during storage(Brodziak et al, 2020). As discussed in the previous paragraph, ESPs can also affect WHC of yoghurt Khider et al (2022). demonstrated the impact of EPSs on the water holding capacity of low-fat yoghurt that was fortified with varying concentrations of EPS derived from Leuconostoc strains, in comparison to a control sample.…”
mentioning
confidence: 86%
See 1 more Smart Citation
“…Furthermore, as discussed in relation to syneresis, it is noteworthy that EPSs can influence the WHC of yoghurt. Using low-fat yoghurt samples, Khider et al (2022) showed that an increase in EPS concentration corresponded to elevated water-holding capacity. In another study, the impact of 0.01% EPSs on the texture and microstructure of buffalo yoghurt indicated that the addition of EPS led to denser casein micelles.…”
Section: Physico-chemical Characteristics and Antioxidative Activity ...mentioning
confidence: 99%
“…Consequently, this approach can obviate the necessity for supplementary stabilizers (Tiwari et al, 2021). An independent study carried out by Khider et al (2022) documented a decrease in syneresis in low-fat yoghurt samples that included EPSs, as opposed to the control group. It is plausible that differences in the experimental conditions utilized in these studies may have played a role in the variations observed in the syneresis index, as proposed by Gezginc et al (2015).…”
Section: Physico-chemical Characteristics and Antioxidative Activity ...mentioning
confidence: 99%